CIVIL SOCIETY DAN STABILITAS SOSIAL: Strategi Forum Lintas Ormas (FLO) dalam Penyelesaian Kasus Pendirian Gereja Batak Karo Protestan (GBKP) di Tanjung Barat, Jakarta Selatan 2016 - Sabhana, Ana (Politeia: Jurnal Ilmu Politik, 2020)
This paper discusses the problem of intolerance that still occurs in Indonesia, one of which is the rejection of the establishment of places of worship. The Karo Protestant Batak Church (GBKP) does not have a permit to build a house of worship, so the surrounding community rejects the building. This paper focus on the strategy undertaken by the Inter-Community Forum (FLO) in resolving the GBKP establishment case, as well as the obstacles that occurred in resolving the GBKP case in 2016 in Tanjung Barat, South Jakarta. This study uses qualitative research methods with analysis and in-depth understanding. Based on the results of the study, the Strategy of the Inter-Organization Forum (FLO) in resolving the Protestant Christian Batak Church (GBKP) case related to the establishment of houses of worship was successfully carried out, through a legal, public and also South Jakarta government approach. Conflicts between religious communities in the West Tanjung area can be avoided, although the Protestant Batak Church (GBKP) cannot establish a church in the region. However, the government has relocated the worship activities of the Protestant Christian Batak Church (GBKP) in the Balai Minggu Sports Hall (GOR) Pasar Rakyat.